Bringing the immigrant back into the sociology of taste. (1st December 2017) - Ray, Krishnendu
Abstract: The sociology of food consumption has emerged as a robust field with rich empirical material and engaged theorization about taste, omnivorousness, distinction, and practice theory. Nevertheless, there are continuing empirical and conceptual lacunae. Although transnational and rural-to-urban migrants play a crucial role in food businesses in many global cities, they are mostly unaccounted for in the sociology of taste. Taking the American case, in particular based on data from New York City, this article provides reasons for that gap and shows what might be gained if migrants were accounted for in the urban sociology of taste.